Emerging Economies and the Emergence of South-South Protectionism - Bown, Chad P. (World Bank, Washington, DC, 2012)
Do exports resume when import-restricting temporary trade barriers such as antidumping are finally removed? To establish the importance of this question for emerging economies, this paper uses newly available data from the World Bank's Temporary Trade Barriers Database to update a number of inter-temporal indicators of import protection along three dimensions: additional time coverage through 2011, additional policy-imposing country coverage, and a more comprehensive depiction of impacted trading partner coverage. It then turns to the emerging economy exporters affected by temporary trade barriers and highlights the economic significance of frequently bilateral import restrictions imposed by other emerging economies, i.e., South-South protectionism. Finally, it then investigates empirically whether country-level exports resume when the previously imposed -- but temporary -- import protection is finally removed. China's exporters respond quickly and aggressively to the market access opening embodied in the removal of such import restrictions. This differs markedly from the slow and tepid export response of other emerging economies, especially when the import protection had been imposed by another emerging economy trading partner. This evidence suggests a previously unidentified long-run cost associated with such South-South protectionism that merits further research and inquiry.